COLLABORATIVE GOVERNANCE UNTUK MEMFASILITASI SERTIFIKAT HALAL PRODUK MAKANAN DAN MINUMAN UMKM KECAMATAN KARAWACI KOTA TANGERANG - Hartati, Yuni; Widyawati, Tito Inneka (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Collaborative governance to facilitate halal certificates for food and beverage products for micro, small and medium enterprises in Karawaci District, Tangerang City, is carried out between the Department of Industry, Trade, Cooperatives and Small and Medium Enterprises of Tangerang City and the Halal Product Guarantee Organizing Agency. The Collaborative governance theory used uses Ansell and Grash's theory regarding the stages in Collaborative governance, namely face-to-face dialogue, building trust, commitment to the process, sharing understanding and expected results. The results of the research provide information. Face-to-face dialogue is carried out with socialization activities. Building trust is carried out by facilitating as well as possible and there are no costs in facilitating halal certification activities for micro, small and medium enterprises. Commitment is built with Stakeholders related to halal certification facilities, namely with business actors where the process of inputting data on requirements regarding product raw materials, product manufacturing processes and other requirements is input by the business actor himself and then accompanied by the Department, the expected results from the halal certification facility are that business actors, especially have legality that can guarantee their products to be widely circulated. There are three obstacles to facilitating halal certification, namely the lack of face-to-face dialogue with the Halal Product Guarantee Organizing Agency, the lack of commitment to implementation, and the limited ability of business actors to understand the importance of halal labeling